PREVALENCE OF ANTI-STREPTOLYSIN O ANTIBODIES AT BANKE REGION NEPAL - Khan, S.; Singh, P.; Siddiqui, A.H. (BALI MEDICAL JOURNAL; Volume 1, Number 3, September-December 2012, 2013)
Objective: Serum levels of anti-streptolysin O antibodies (ASO) in the routine evaluation of patients with rheumatic conditions. Prevalence of elevated serum ASO titer in patients which were coming in OPD & IPD of Nepalgunj Medical College & teaching hospital with various clinical conditions. Method : This was a retrospective cross sectional study, which was performed in the central laboratory of Microbiology at Nepalgunj Medical College and teaching Hospital, Banke, Nepal during the period of September 2010 to April 2012. The serum samples were tested for Antistreptolysin O (ASO) antibodies by latex agglutination test. Results : Total 308 patients including 40.91% male and 50.09% female  were tested for ASO serum levels.140 were positive and 168 were negative .In 140 positive cases 57 were male and 83 were female. In 168 negative cases 69 were male and 99 were female. Conclusion: The prevalence of Anti-streptolysin O (ASO) antibody in total cases was 45.45%.In male was 45.24% and in female was 45.60%.the highest percentage was found in age group 0-21years. The presence of elevated streptococcal antibody titers in such a population, which probably re?ects a high background prevalence of streptococcal infections, should be taken into consideration when evaluating the role of the group A streptococcus in non-purulent complications of infections.
Keywords: Prevalence, Anti-streptolysin O (ASO), group A Streptococcus (GAS), rheumatic diseases, Banke Region.